Travel Preferences of Millennials in a Highly Urbanized City in the Philippines - Ruña, Candy B.; Diamante, Angelus C. (Philippine Social Science Journal, 2020)
Travel preferences are activities and places that people would like to do and go to. Millennials, who are also referred to as Generation Y, greatly impact the travel and tourism industry as they reach their peak earning years and spending power. They travel more frequently, explore more destinations, and constantly search for information and new sensations. Nowadays, they are active travelers who are starting to build travel motivations and influence their opinions and behavior. To tap this market, it is important for tourism stakeholders to understand millennials and their travel preferences. Hence, this paper describes the degree of travel preferences of millennials of a highly urbanized city in the Philippines in terms of attractions, type of accommodation, transportation, food and beverage, ancillary services, and travel budget. Likewise, it explores the relationship between demographics and travel preferences. It also determines millennials’ travel purpose, preferred destinations, travel lifestyle, and other factors that influence their travel.